OCCUPATIONAL SAFETY AND HEALTH INSPECTION PROGRAM ACHIEVEMENT OF SAFETY CULTURE IN NOODLES INDUSTRY PT ABC SEMARANG - Seviana Rinawati; Rizky Aristana Maharani; Reni Wijayanti (Universitas Darussalam Gontor, 2017)
Noodle industry in production process activity there were hazard risk factors caused work accident and work-related diseases due to unsafe action and unsafe condition. Prevention efforts the company through by the OHS inspection program to realize the safety culture so as to suppress the occurrence of unsafe behavior. The purpose of this study was to know the OHS inspection program in the achievement of safety culture in the noodle industry. This research employed a descriptive method to describe the implementation of occupational safety and health inspection program as the attempt of creating safety culture observed through data, interview and direct observation then analyzed with related regulation. Results of research in the noodle industry PT. ABC Semarang has implemented OHS inspection program consisting of informal inspection and planned inspection such as safety patrol and special inspection. Based on the analysis of accidents caused, observations and interviews can be seen that safety culture has not been formed properly. It can be seen from the average of work accident caused by unsafe action and labor behavior in using Personal Protective Equipment (PPE) which still not in accordance the regulations. The Company has applied occupational safety and health inspections program corresponding to Government Regulation, however occupational safety and health inspection program has been able create safety culture in company environment. Thus, the company should restudy the occupational safety and health inspections program and improve the effectiveness of occupational safety and health inspection program implementation. Keywords : Occupational Safety and Health Inspection program, Safety Culture